Compilation Tape
A compilation of short films from 1992 and 1993, shot during the siege of Sarajevo by a group of multi-ethnic film makers from Sarajevo (SAGA). The film includes the following SAGA productions: 1. “Anđeli u Sarajevu” (“Angels in Sarajevo”), Antonije Nino Žalica, September 1993, 7 min. 2. “Smjesa za preživljavanje” (“Survival Brew”), Mehmed Aksamija, August 1993, 10 min. 3. “Čekajući paket” (“Waiting for Parcels”), Vuk Janić, 1993, 11 min. 4. “Skitnice i psi” (“Bums and Dogs”), Zlatko Lavanić, June 1993, 26 min.